A COMPARATIVE ANALYSIS OF UZBEK COMMUNICATION WITH SPECIFIC CULTURES: WESTERN, AMERICAN, JAPANESE, AND SLOVAKIAN PERSPECTIVES - Ozodaxon O'ktamova Ilhomjon qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Abstract: This article provides a comparative analysis of Uzbek communication with Western, American, Japanese, and Slovakian cultures. Drawing on cultural dimensions, face negotiation theory, and contextual factors, the analysis reveals distinct communication styles shaped by historical, social, and religious backgrounds. Uzbek communication is characterized by indirectness, formality, and respect for hierarchy, contrasting with the directness and informality of Western and American styles. Japanese communication emphasizes harmony and non-verbal cues, while Slovakian communication values warmth and personal relationships. Understanding these differences is essential for effective cross-cultural communication, leading to more meaningful and productive interactions.